Pregnant women in the exposure to COVID-19 infection outbreak with the risk of stunting based on the growth and development of babies - Suryani Manurung (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Exposure to Covid-19 that occurs in pregnancy is at risk of miscarriage, IUGR (intrauterine growth retardation) and as a predictor of detection of stunted babies associated with pregnancy and postpartum.Purpose: To analyze pregnant women in the exposure to the COVID-19 infection outbreak with the risk of stunting based on the growth and development of babiesMethod: The cross-sectional population is infants aged less than 12 months and their mothers with a history of Covid-19 infected status during pregnancy. The samples were 48 two groups of infectious and non-infectious and taken by a purposive sampling technique. Researched at the polyclinic of the Covid-19 referral hospital. The statistic analyzes mean and correlation test data with Chi-Square.Results: The age range of babies at observation was 2-12 months with a mean age of 7 months. Progression score with Pre-screening Developmental Questionnaire (PDQ) lowest 2 and highest 10. Pregnant women who are not infected are at risk of stunting with the highest indicator of baby weight is normal at 70.8 percent and normal baby height at 80 percent. Pregnant women infected with Covid-19 without symptoms to moderate symptoms risk stunting with the highest indicator of baby weight being normal ranging from 46.2 percent – 80 percent and normal infant height ranging from 80 percent - 84.6 percent. Analysis of the effect of exposure to Covid-19 during pregnancy on the risk of stunting based on the baby's weight and height had no effect (p-value > 0.05). The ratio of infant development deviations in uninfected and Covid-19 infected mothers was 16.7%. The results of the analysis of the relationship between the confirmed status of Covid-19 during pregnancy and infant development are related (P value < 0.05).Conclusion: The effect of exposure to Covid-19 during pregnancy on the risk of stunting based on the baby's weight and height has no effect. A comparison found deviations in infant development in uninfected and Covid-19-infected mothers, there was an association.